2021
DOI: 10.52922/ti78306
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and predictors of reoffending among child sexual offenders: a rapid evidence assessment

Abstract: A rapid evidence assessment was conducted to provide an updated review of reoffending research on child sexual offenders from January 2010 to March 2020. Thirty-three studies examining 55 independent samples of adult and juvenile child sexual offenders were reviewed. Across most studies, rates of sexual reoffending were 15 percent or less, and rates of general reoffending were between 20 and 54 percent. The evidence suggests that the cumulative likelihood of both general and sexual reoffending increases until … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Contact offenders were more likely to have access to children, score higher on antisocial personality measures, and more frequently commit minor offenses, than CSAM-only offenders. Additionally, Dowling et al (2021) found that only a small proportion of CSAM-only offenders subsequently commit a contact child sexual offense.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Contact offenders were more likely to have access to children, score higher on antisocial personality measures, and more frequently commit minor offenses, than CSAM-only offenders. Additionally, Dowling et al (2021) found that only a small proportion of CSAM-only offenders subsequently commit a contact child sexual offense.…”
Section: Literature Reviewmentioning
confidence: 99%